ANALISIS MODEL TRANSFER TACIT KNOWLEDGE: STUDI KASUS DIVISI PRODUCTION PLANNING CONTROL PT X - Rumanti, Augustina Asih (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
Transfer tacit knowledge is one way to utilize and conserve organizationâs tacit knowledge.Â The organization must use and keep tacit knowledge because it is a competitive advantage sources.Â A model of transfer tacit knowlegde will help organization to manage and empower tacitÂ knowledge. The article explains a model of transfer tacit knowledge that focussing on transferÂ process of tacit knowledge among individuals in one division. The model consists of six contructs:Â sources characteristics, receiver characteristics, tacit knowledge characteristics, organizationÂ context, media characteristics, and the effectiveness of transfer tacit knowledge. The validationÂ model is conducted in one company that making wire in Indonesia. Respondents are the membersÂ of Production Planning Control division. Data managemaent is conducted through StructuralÂ Equation Modelling method along with Planning Control. The data result shows that the influentialÂ key factor towards the effectiveness transfer tacit knowledge process among individuals in oneÂ division is the ability of teaching sources, receiver absorbency, evidence and trust.